Differentiated approach in the treatment of diffuse large B-cell lymphoma according to c-MYC and BCL2 status - R. K. Karakulov; D. R. Kaydarova; Z. D. Dushimova; S. T. Gabbasova; G. A. Sagindykov; B. A. Nasipov; A. S. Dzhazyltaeva; N. A. Kemelbekov (Онкогематология)
Background. The treatment results of patients with diffuse large B-cell lymphoma (DLBCL) with c-MYC proto-oncogene and BCL2 protein positivity according to the CHOP-21 ± R scheme remain unsatisfactory, which dictates the need to intensify the therapy regimen. Due to the fact that most authors combine DH (double hit) lymphomas and DE (double expressor) lymphomas for analysis, these data do not allow forming an accurate idea of the independent significance of the phenomenon of activated transcription factor c-MYC and BCL2 protein in patients with DLBCL and the results of treatment specifically in this group. Some researchers believe that the presence of c-MYC gene aberration and BCL2 protein expression are associated with negative clinical characteristics. Nevertheless, the clinical features of this subgroup of DLBCL remain poorly understood.The objective of the study was to analyze the incidence of c-MYC gene aberrations, BCL2 expression in DLBCL patients and to evaluate the effectiveness of intensive R + Hyper-CVAD chemotherapy regimen in this group of patients.Materials and methods. We analyzed the data of 80 patients aged 18–65 years with a newly diagnosed DLBCL for the period from 2018 to 2020. The diagnosis was established by histological and immunohistochemical examination. The tumor stages (II–IV) were assessed according to the Ann Arbor classification; the patient’s somatic status – according to the ECOG scale with a total of no more than 3 points. To detect c-MYC gene aberrations in the tumor tissue, fluorescent in situ hybridization was performed; to determine the BCL2 protein expression and Ki-67 proliferative index – an immunohistochemical study was performed. Patients with identified c-MYC gene aberrations received treatment, which included 8 courses of polychemotherapy according to the R + Hyper-CVAD scheme and high-dose chemotherapy according to the BFR scheme with autologous hematopoietic stem cell transplantation. Patients with DLBCL, in whom c-MYC gene aberration was not detected, were assigned to the group of intermediate and low malignancy. They received a polychemotherapy regimen according to the R-CHOP-21 scheme (up to 8 courses).Results and conclusion. For the first time in Kazakhstan, we studied the incidence of c-MYC proto-oncogene aberrations, BCL2 protein expression and proliferative activity (Ki-67) in DLBCL patients, which made it possible to identify groups of highly aggressive tumor and intermediate, low malignancy, apply personalized polychemotherapy programs and evaluate the immediate treatment efficacy. This approach made it possible to increase treatment effectiveness in the group of patients with highly aggressive DLBCL and to achieve comparable results with therapy in patients with a more favorable prognosis.